Aeschylus: Persians - Rosenbloom, David (Duckworth companions to Greek and Roman tragedy, 2021)
Aeschylus' Persians is the earliest extant Greek tragedy and sole surviving historical tragedy. It tells the story of the Persian king Xerxes' disastrous invasion of Greece in 480/79 and dramatises his return to Persia in rags to face the condemnation of his elders and to lament his defeat. The first Western depiction of the causes and limits of imperialist conquest, the Persians is especially relevant today. The play is unflinching in its portrayal of the horrors of the Persian defeat, but it is not merely a paean to Western freedom, democracy, courage and military supremacy; it is a meditation on the tendency of wealth, power and success to take on a momentum of their own and to push societies to the brink of ruin. This companion to the play provides historical context, thematic discussion, literary and performance history, bibliography and glossary. It is entirely accessible to those studying the play in translation as well as the original Greek.--Back cover.